(untitled) (Itinera, 2013)
Paper aims to show how traditional dramaturgic concepts can be re-used to study a dramaturgy of image in the contemporary theatrical forms. When dialogue, action and conflict appear into the image, they highlight a dramaturgic movement towards the spectator. We also remark that mimesis and recognition are questioned, and emotions tend to replace comprehension. It could also be claimed that there is a symptom-effect in perception, if we open the argument to psychoanalysis, as G. Didi-Huberman claimed, as well as to Bachelard’s “reader-dreamer” model.